Fabrication of a Miniature Zinc Aluminum Oxide Nanowire Array Gas Sensor and Application for Environmental Monitoring - Chin-Guo Kuo; Chi-Wu Huang; Jung-Hsuan Chen; Yueh-Han Liu (International Journal of Photoenergy)
A miniature n-type semiconductor gas sensor was fabricated successfully using zinc aluminum oxide nanowire array and applied to sense oxygen. The present study provided a novel method to produce zinc aluminum alloy nanowire 80 nm in diameter by the vacuum die casting technique and then obtain zinc aluminum oxide nanowire array using the thermal oxidation technique. The gas sensing properties were evaluated through the change of the sensitivity. The factors influencing the sensitivity of the gas sensor, such as the alloy composition, operating temperature, and oxygen concentration, were investigated further. Experimental results indicated that the maximum sensitivity could be acquired when the weight percentage of aluminum was 5% in zinc aluminum alloy at the operating temperature of 200°C.